A literature review of the impact and implication of out-migration on rural agriculture in South Africa - Mbatha, Mfaniseni Wiseman; Mofokeng, Neo R. (Penerbit Universiti Kebangsaan Malaysia, 2021)
The acceleration of out-migration from rural to urban areas has a negative impact on the productivity and development of rural agriculture in developing countries. This is because out-migration hinders surplus labour and engenders low rural agricultural income. This study reviews literature on the impact and implications of out-migration on rural agriculture in South Africa, a developing country. The study is qualitative and applies the principles of case-study research for design purposes. The research is underpinned by Lee’s (1966) Push-Pull Theory. Lee’s Push-Pull Theory has been effective in guiding arguments and discussions on the impact and implications of out-migration on rural agriculture. The findings reveal that the loss of human capital through out-migration results in low rural agricultural productivity in developing countries. The changing climate conditions also constitute a primary push factor for people’s out-migration from rural areas, resulting in rural agriculture’s loss of human capital. This is because people involved in rural agriculture lack alternative strategies that they can use to cope with the consequences of climate change. Nonetheless, out-migration could contribute positively to rural agriculture through remittances that people could use to purchase agricultural inputs. Hence, rural dwellers need to be provided with appropriate financial literacy concerning the relationship between migration and remittances. This could increase rural households’ savings and thus enable them to invest in rural agriculture.